End-tidal and arterial carbon dioxide gradient in serious traumatic brain injury after prehospital emergency anaesthesia: a retrospective observational study. Issue 11 (14th September 2020) - Price, James; Sandbach, Daniel D; Ercole, Ari; Wilson, Alastair; Barnard, Ed Benjamin Graham
Abstract : Objectives: In the UK, 20% of patients with severe traumatic brain injury (TBI) receive prehospital emergency anaesthesia (PHEA). Current guidance recommends an end-tidal carbon dioxide (ETCO2 ) of 4.0–4.5 kPa (30.0–33.8 mm Hg) to achieve a low-normal arterial partial pressure of CO2 (PaCO2 ), and reduce secondary brain injury. This recommendation assumes a 0.5 kPa (3.8 mm Hg) ETCO2 –PaCO2 gradient. However, the gradient in the acute phase of TBI is unknown. The primary aim was to report the ETCO2 –PaCO2 gradient of TBI patients at hospital arrival. Methods: A retrospective cohort study of adult patients with serious TBI, who received a PHEA by a prehospital critical care team in the East of England between 1 April 2015 and 31 December 2017. Linear regression was performed to test for correlation and reported as R-squared (R 2 ). A Bland-Altman plot was used to test for paired ETCO2 and PaCO2 agreement and reported with 95% CI. ETCO2 –PaCO2 gradient data were compared with a two-tailed, unpaired, t-test. Results: 107 patients were eligible for inclusion. Sixty-seven patients did not receive a PaCO2 sample within 30 min of hospital arrival and were therefore excluded. Forty patients had complete data and were included in the final analysis; per protocol. The mean ETCO2 –PaCO2 gradient was 1.7 (±1.0) kPa (12.8 mm Hg), with moderate correlation (R 2 =0.23, p=0.002). The Bland-Altman bias was 1.7 (95% CI 1.4 to 2.0) kPa with upper and lower limits of agreement of 3.6 (95% CI 3.0 to 4.1) kPa and −0.2 (95% CI −0.8 to 0.3) kPa, respectively. There was no evidence of a larger gradient in more severe TBI (p=0.29). There was no significant gradient correlation in patients with a coexisting serious thoracic injury (R 2 =0.13, p=0.10), and this cohort had a larger ETCO2 –PaCO2 gradient, 2.0 (±1.1) kPa (15.1 mm Hg), p=0.01. Patients who underwent prehospital arterial blood sampling had an arrival PaCO2 of 4.7 (±0.2) kPa (35.1 mm Hg). Conclusion: There is only moderate correlation of ETCO2 and PaCO2 at hospital arrival in patients with serious TBI. The mean ETCO2 –PaCO2 gradient was 1.7 (±1.0) kPa (12.8 mm Hg). Lower ETCO2 targets than previously recommended may be safe and appropriate, and there may be a role for prehospital PaCO2 measurement.